Building the Sociopreneurship Spirit of the Luba Hilir Hamlet Community in Koto Tinggi Village Based on E-Marketing on Handicraft Products from Palm Oil Waste Sticks - Rena Lestari; Lusi Eka Afri; Masdi Janiarli; Yuliana Safitri; Sri Wahyuningsih (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Rokan Hulu Regency is the district with the largest number of oil palm plantations in Riau Province. With the vast amount of palm oil causing palm oil waste that has an impact on environmental damage. A group of dasawisma women make handicrafts by utilizing palm oil waste. The purpose of this service is to increase the capacity of science and technology, counseling and mentoring regarding e-marketing, making a logo of the products produced. The methods used are location surveys and discussions, increasing the capacity of science and technology in the production system, training and socialization, and evaluation. The results of the service showed an increase in partner empowerment where partners understood 76% of the material presented based on the questionnaire given. Increased knowledge about digital marketing through Facebook, Instagram and TikTok platforms. The availability of stick-shaving machine facilities and increased partner knowledge in e-marketing and increasing product yields. The satisfaction survey analysis showed a very satisfied category with a value of 92.03%.